PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR TKJ SISWA KELAS X SMK IT AGUS SUSANTO PASAMAN BARAT - Halima Halima; Zulfani Sesmiarni; Wedra Aprison; Supratman Zakir (KOLONI, 2022)
This research is motivated by student learning outcomes that are still low, and students lack the courage to express their opinions, namely to find out whether students' learning outcomes of computer and network engineering by applying think pair share type cooperative learning model are better than students' computer and network engineering learning outcomes without apply a cooperative learning model of think pair share type for class X students of SMK IT Agus Susanto. This research is an experimental research. The population of this study were students of class X TKJ SMK IT Agus Susano in the 2021/2022 academic year. The sampling technique was carried out by purposive sampling. Selected class X TKJ 1 as the Experiment class and class TKJ 2 as the Control class. The instrument used is a final test in the form of an essay to test the hypothesis using a t-test before being tested for normality and tested for homogeneity with test reliability r_11 = 0.860. The final test analysis showed that both samples were normally distributed and homogeneous. The statistical test used for hypothesis testing is the one-party t-test. The results of hypothesis testing obtained t_count = 0.988 Greater than t_table = 1.676, because t_count> t_table, the research hypothesis is accepted with a 95% confidence interval. Thus, it is accepted that students' learning outcomes of computer and network engineering applying think pair share type cooperative learning model are better than students' computer and network engineering learning outcomes applying think pair share cooperative learning model class X TKJ SMK IT Agus Susanto, West Pasaman Regency. Keywords: Cooperative, Think Pair Share Type, Students